Prevalence of Anaplasma marginale in cattle blood samples collected from two important livestock regions in Punjab (Pakistan) with a note on epidemiology and phylogeny of parasite - Zafar, Shahzadi Noor Ul Ain; Khan, Adil; Niaz, Sadaf; Aktas, Munir; Ozubek, Sezayi; Farooq, Muhammad; Swelum, Ayman A. (Elsevier, 2022)
Anaplasmosis, caused by intracellular gram-negative bacteria Anaplasma marginale is one of the most frequently reported tick-borne disease (TBDs) in tropical and sub-tropical countries, including Pakistan. In the present study, a total of 428 cattle blood samples were collected to examine the prevalence and phylogenetic origin of A. marginale in two important livestock regions of Punjab Province in Pakistan, i.e. Lodhran and Dera Ghazi Khan Districts. In addition, association between occurrence of A. marginale in cattle blood and selected epidemiological factors has been also investigated. The presence of A. marginale genetic material was confirmed in 9% of the tested blood samples taken from cattle in Lodhran and in 17% from Dera Ghazi Khan. Prevalence of A. marginale was significantly higher in cattle from Dera Ghazi Khan. All the cattle breeds from both districts were equally susceptible to A. marginale infection. We reported higher prevalence of A. marginale in cattle living indoors or with other dairy animals in Dera Ghazi Khan district. However, no such relationship was observed in the Lodhran district. Sequencing of the msp1b gene shows 96-99% similarity of A. marginale in the study area to those reported from other parts of Pakistan, South Africa, and Israel. We recommend that large scale tick and tick-borne disease control strategies must be implemented in both districts. (c) 2021 The Author(s). Published by Elsevier B.V. on behalf of King Saud University. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Molecular characterization; Cattle; Punjab; Pakistan